WHAT DO YOU WEIGH? POPULAR FEMINISM AND BODY POSITIVITY AS MEDIATED DISEMBODIMENT - Taylor, Hannah; Meisner, Colten (AoIR Selected Papers of Internet Research, 2020)
This study analyzes the Instagram page, @i_weigh, and its relation to body positivity discourses. Drawing on a visual discourse analysis of 300 Instagram posts from the @i_weigh account, this study suggests that body positivity movements may be increasingly disembodied in a self-representational era hallmarked by popular feminism. On 16 March 2018, actress and activist Jameela Jamil posted a photo to Instagram, obscuring her body with textual identifiers like “great friends” and “I laugh every day.” This post marked the launch of the Instagram account @i_weigh. This page, founded and maintained by Jamil, posts submissions from Instagram users answering the call to “weigh” themselves beyond the corporeal. This movement, now millions in reach, signals a departure from the conventions of body positivity. Rather than discovering empowerment through the body, @i_weigh encourages its participants to publicly privilege external relationships, social identities, and economic opportunities in an effort to look past the body. @i_weigh discursively constructs a mediated disembodiment, characterized by its liminal visual representation and categorization of the self through narratives of resilience and strength, claiming marginalized identities, and extra-self connection. The interaction of liminality and mediated disembodiment is reflective of self-representation in an age of popular feminism, placing the responsibility back on women for their own empowerment and production of selfhood while ignoring the socio-cultural frameworks that create a need for empowerment in the first place.